2020
DOI: 10.3168/jds.2019-16851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sequestering agents based on a Saccharomyces cerevisiae fermentation product and clay on the ruminal bacterial community of lactating dairy cows challenged with dietary aflatoxin B1

Abstract: This study was conducted to examine the effects of clay (CL) and Saccharomyces cerevisiae fermentation product (SCFP) on the ruminal bacterial community of Holstein dairy cows challenged with aflatoxin B 1 (AFB 1 ). A second objective was to examine correlations between bacterial abundance and performance measures. Eight lactating dairy cows stratified by milk yield and parity were randomly assigned to 4 treatments in a 4 × 4 Latin square design with 2 replicate squares, four 33-d periods, and a 5-d washout be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
3
3
0
1
Order By: Relevance
“…Muribaculaceae is a family of bacteria that produces enzymes capable of degrading complex carbohydrates and has been reported to produce short-chain fatty acids(Barouei et al, 2017;Obanda et al, 2018), which play important roles in regulating immune function and energy metabolism. A recent study revealed that the abundance of Muribaculaceae in the rumen is positively correlated with feed e ciency and other production traits such as milk components(Jiang et al, 2020) and negatively correlated with methane production in Holstein dairy cows(Cunha et al 2017).As seen in our result, the relative abundance of Moryella was greater and that Clostridium_sensu_stricto_1 was lower in low-RFI compared to high-RFI. Previous studies have shown that species of Moryella play a key role in the breakdown of complex carbohydrates and the production of volatile fatty acids (VFAs) such as acetate, propionate, and butyrate, which are important energy sources that support improved health and performance of ruminants(Carlier et al, 2007;Hu et al, 2020).A study correlating individual RFI values with bacterial abundances in feces reported that Clostridium I is associated with high RFI in chickens(Siegerstetter et al, 2018;Liu et al, 2021).…”
supporting
confidence: 72%
“…Muribaculaceae is a family of bacteria that produces enzymes capable of degrading complex carbohydrates and has been reported to produce short-chain fatty acids(Barouei et al, 2017;Obanda et al, 2018), which play important roles in regulating immune function and energy metabolism. A recent study revealed that the abundance of Muribaculaceae in the rumen is positively correlated with feed e ciency and other production traits such as milk components(Jiang et al, 2020) and negatively correlated with methane production in Holstein dairy cows(Cunha et al 2017).As seen in our result, the relative abundance of Moryella was greater and that Clostridium_sensu_stricto_1 was lower in low-RFI compared to high-RFI. Previous studies have shown that species of Moryella play a key role in the breakdown of complex carbohydrates and the production of volatile fatty acids (VFAs) such as acetate, propionate, and butyrate, which are important energy sources that support improved health and performance of ruminants(Carlier et al, 2007;Hu et al, 2020).A study correlating individual RFI values with bacterial abundances in feces reported that Clostridium I is associated with high RFI in chickens(Siegerstetter et al, 2018;Liu et al, 2021).…”
supporting
confidence: 72%
“…Tong et al 35 reported that Ruminococcus 2 and Muribaculaceae are relatively more abundant in dairy cows with higher milk yields. Another study reported that the abundance of Treponema and Muribaculaceae in the rumen is positively correlated with milk yield, milk fat content, milk protein content, and feed efficiency in dairy cows 36 . Furthermore, Cunha et al 37 suggested that the presence of Schwartzia , Treponema, and Muribaculaceae is negatively correlated with methane production in Holstein cows.…”
Section: Discussionmentioning
confidence: 98%
“…Muribaculaceae is a family of bacteria that produces enzymes capable of degrading complex carbohydrates and has been reported to produce short-chain fatty acids [ 38 , 39 ], which play important roles in regulating immune function and energy metabolism. A recent study revealed that the abundance of Muribaculaceae in the rumen is positively correlated with feed efficiency and other production traits such as milk components [ 40 ] and negatively correlated with methane production in Holstein dairy cows [ 41 ].…”
Section: Discussionmentioning
confidence: 99%